2019
DOI: 10.1007/s40820-019-0294-9
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Conductive Anodes Based on 3D Hierarchical Sn/NS-CNFs@rGO Network for Sodium-Ion Batteries

Abstract: HIGHLIGHTS • 3D hierarchical conductive Sn quantum dots encapsulated in N,S co-doped carbon nanofibers sheathed within rGO scrolls (Sn/NS-CNFs@rGO) were prepared through an electrospinning process. • Flexible Sn/NS-CNFs@rGO electrode exhibits superior long-term cycling stability and high-rate capability in sodium-ion batteries. ABSTRACT Metallic Sn has provoked tremendous progress as an anode material for sodium-ion batteries (SIBs). However, Sn anodes suffer from a dramatic capacity fading, owing to pulveriza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(29 citation statements)
references
References 53 publications
1
28
0
Order By: Relevance
“…The result is also in accordance with that of XRD patterns. In Figure 2(e, f) and Figure S6(b, c), the C 1s peak shows the coexistence of three major characteristic peaks at about 284.84, 286.94 and 288.55 eV, which agree with C−C, C−O and O−C=O functional groups, respectively [44,45] . However, the intensity of oxygen‐containing functional groups of sparked rGO, HrGO‐1, HrGO‐2 and HrGO‐4 films is lower than that of pristine GO, HGO‐1, HGO‐2 and HGO‐4 films, indicating that the oxygen‐containing functional groups are expelled by spark reaction.…”
Section: Resultsmentioning
confidence: 85%
“…The result is also in accordance with that of XRD patterns. In Figure 2(e, f) and Figure S6(b, c), the C 1s peak shows the coexistence of three major characteristic peaks at about 284.84, 286.94 and 288.55 eV, which agree with C−C, C−O and O−C=O functional groups, respectively [44,45] . However, the intensity of oxygen‐containing functional groups of sparked rGO, HrGO‐1, HrGO‐2 and HrGO‐4 films is lower than that of pristine GO, HGO‐1, HGO‐2 and HGO‐4 films, indicating that the oxygen‐containing functional groups are expelled by spark reaction.…”
Section: Resultsmentioning
confidence: 85%
“…Many efforts have focused on constructing 3D structures. [91,92] For instance, Chen et al [91] developed graphitic porous carbon nanocages (PCNCs) in which Sn nanoparticles were encapsulated by a template-assisted CVD and in-site reduction method. The PCNCs could restrict Sn particle aggregation and provide sufficient buffering space for volume expansion, as shown in Figure 8a.…”
Section: D Porous Sn-c Compositesmentioning
confidence: 99%
“…Theoretical calculations showed that a strong bond forms between amorphous carbon black and Na 15 Sn 4 during cycling, which accelerates bare Sn electrode pulverization, whereas graphitic carbon layers in the electrodes show weak interactions with Na 15 Sn 4 and are more favorable to the cycling performance by preventing CNC‐Sn electrode pulverization. As a result, the PCNCs‐Sn exhibited a high reversible capacity of 828 mA h g −1 at 0.047 C and a long cycle life up to 1000 cycles even at 3 C. More recently, a flexible 3D hierarchical conductive network electrode that consists of 0D Sn quantum dots, 1D N, S‐doped carbon nanofibers and 2D RGO was designed (denoted Sn/NS‐CNFs@RGO) , [ 92 ] as shown in Figure 8e. Because of the restriction and buffering effects of NS‐CNFs and RGO materials, severe Sn particle agglomeration and volume changes during cycling were hindered.…”
Section: Structural Designs Of Sn‐based Materials For Stable Sodium S...mentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the multiphase nanocomposites prepared by encapsulation strategies were expected to be of satisfactory reversible capacity. As shown in Figure 11A(a–b), a flexible 3D hierarchical composite membrane electrode (Sn/NS‐CNFs@rGO) has been fabricated with Sn NPs encapsulated in N,S co‐doped CNFs sheathed within rGO scrolls [99b] . The introduction of N and S atoms in CNFs brings more defects, which help enhance electronic conductivity and offer more active sites for storage of sodium ions.…”
Section: Application Of 3d‐carbon In Sibs Electrode Materialsmentioning
confidence: 99%